Effect of sialoadenectomy and synthetic human urogastrone on healing of chronic gastric ulcers in rats. Issue 12 (December 1986) - Olsen, P S; Poulsen, S S; Therkelsen, K; Nexø, E
Abstract : The effect of extirpation of the submandibular glands, an exocrine organ for epidermal growth factor/urogastrone (EGF/URO), and the effect of oral administration of synthetic human (EGF/URO) on healing of chronic gastric ulcers in rats has been investigated. Removal of the submandibular glands delayed healing of chronic gastric ulcers when examined after 50, 100, and 200 days. Oral administration of synthetic human EGF/URO stimulated gastric ulcer healing when examined after 25 and 50 days of treatment. The effect of synthetic human EGF/URO was comparable with that of cimetidine. The combined administration of synthetic human EGF/URO and cimetidine further increased healing of gastric ulcers compared with administration of each substance. Neither synthetic human EGF/URO, nor removal of the submandibular glands had any influence on gastric acid secretion. This study showed that the submandibular glands influence healing of chronic gastric ulcers and suggest that EGF/URO participate in healing of chronic gastric ulcers in rats.